Faktor yang Berhubungan dengan Kejadian Computer Vision Syndrome pada Karyawan Bank - Nopriadi, Nopriadi; Pratiwi, Yuharika; Leonita, Emy; Tresnanengsih, Erna (Media Kesehatan Masyarakat Indonesia, 2019)
Computer Vision Syndrome (CVS) is a collection of compound eye symp-toms due to using a computer. According to the initial survey, more than three quarter officers of Bank RK in Pekanbaru who daily work using computers experience CVS. This study aimed to determine factors associated with CVS. This type of study was quantitative observational with cross-sectional design with amount of sample 117 respondents. Data analysis used was univariate, chi-square used for bivariate analysis and multiple logistic regression used for multivariate analysis. Based on the chi-square analysis the results showed that Bank RK officers who experienced CVS complaints were in the forms of tired and tense eyes at 54,3%, neck pain at 28,7%, shoulder pain at 27, 7%, headache at 25,5%, blurred vision at 20,2%, seeing twins at 17%, watery eyes and difficulty to focus at 14,9%, back pain at 11,7%, sore eyes, irritation pain at 5,3%. Variables related to CVS were vision distance (p=0.016), monitor position (p=0.011), lighting (p=0.001), working period (p=0.002), the length of work (p=0.000). Variables not related to CVS was age (p=0.561). Variable of the length of work with computers ≥4 hours a day was 9 times riskier of causing CVS in Bank RK officers. This study indicates that the most dominant factor influential to CVS is the length of work, while other factors that act as confounding that affect CVS are monitor position, the lighting of the work station, the period of working with computer.